Tracheomalacia in patients undergoing thyroid surgery—What is the true estimate: A systematic review and meta‐analysis - Shayan Khalid Ghaloo; Syed Shabbir Afzal; Syed Akbar Abbas; Shayan Ansari; Mriganka De; Haissan Iftikhar (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objectives Tracheomalacia is defined as the weakening of the tracheal rings secondary to long‐standing compression or inherent structural weakness, leading to stridor and airway compromise. The common etiological factor of tracheomalacia includes compression of the tracheal framework due to a large multinodular goiter. There are various management techniques described in the literature to manage a patient with tracheomalacia including tracheostomy, tracheal stenting, and tracheopexy. However, the evidence of tracheomalacia in the literature is conflicting. Therefore, a systematic review was conducted to estimate the incidence of tracheomalacia after thyroidectomy. Methods The systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. A literature search was performed on PubMed, Web of Science, Cochrane library, and Elton B. Stephens Co. cumulative index to nursing and allied health literature plus to determine the incidence of tracheomalacia among patients undergoing thyroidectomy up till October 2021. The eligibility was assessed by two independent authors. A quality assessment of individual studies was performed using the National Institute of Health quality assessment tool. Outcomes were double data extracted and were analyzed using OpenMeta. Results The online search retrieved 214 papers, out of which 17 studies were included that fulfilled the eligibility criteria. The number of patients included in the systematic review who underwent thyroidectomy was 1108. The mean age was 55.8 ± 7.7 years, ranging from 48 to 75 years. Tracheomalacia was reported in 146 patients (1.4%). Sternotomy was performed in 102 patients to approach the goiters with retrosternal extension. The most common intervention to manage tracheomalacia was tracheostomy or prolonged intubation. Conclusions Tracheomalacia is a rare complication. In cases where tracheomalacia is encountered, common methods of management include tracheostomy or prolonged endotracheal intubation. Prospective, long‐term studies are required to accurately assess its true incidence and associated factors.